The development of the artist-ideal in Europe at the turn of the 19th–20th century: Transformations in Hungary and their musical aspects - Dévai, Adrienn; Pethő, Villő; Czabaji Horváth, Attila (Gyermeknevelés Tudományos Folyóirat, 2025)
--